PRODUK PEMIKIRAN HUKUM ISLAM INDONESIA (Telaah dalam Prespektif Kearifan Lokal) - Rasyid, Muh. Haras (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2011)
This article titled Product of Islamic Legal Thought Indonesian (already in the perspective of local wisdom). Gave birth to a subject heading as â€œHow the Islamic Legal Thought Indonesian Products from the perspective of local wisdomâ€ To solve the existing problem, use multiple methods and approaches, including: methods of data collection and analysis as well as juridical and sociological approach. The next process is carried out a description of the products of Indonesian Islamic legal thought, which is based on religious law, fatwa, jurisprudence, and law. The followed a discussion of local knowledge into consideration in the product of Islamic legal thought known through the work of the clergy in general and local knowledge in the products of Islamic legal thought, especially in Indonesian. In the end, the produc of legal thought Islamic Indonesian remains under Alquran and hadith and is also not free from the influence of local knowledge or the d